Perkembangan Tafsir Al-Qur’an di India dan Pakistan: Studi Regional terhadap Tradisi Keilmuan Islam - Imron Taslim; Lukman Nul Hakim; Taslim, Imron (AL-BAYAN INSTITUTE, 2025)
This study examines the development of Qur’anic exegesis (tafsir) in India and Pakistan, focusing on the Islamic scholarly traditions that have evolved in these regions. Employing a qualitative research method with literature review and text analysis, the study explores the characteristics, socio-cultural contexts, and intellectual dynamics within the tafsir traditions of South Asia. Findings reveal that tafsir in India predominantly emphasizes spiritual and Sufi approaches, whereas in Pakistan, tafsir development centers on legal and social aspects influenced by Islamic reformist movements. The advancement of digital technology has further expanded access and enriched scholarly dialogue on tafsir in both countries. This research also identifies a significant academic gap regarding comprehensive studies on Qur’anic exegesis in this region, highlighting the need for further in-depth investigation to enhance understanding of South Asian Islamic scholarship. The findings contribute valuable insights to the broader corpus of Qur’anic interpretation and support inter-cultural and inter-religious dialogue in the contemporary era